2001
DOI: 10.1002/ajim.1084.abs
|View full text |Cite
|
Sign up to set email alerts
|

Work environment factors, health, lifestyle and marital status as predictors of job change and early retirement in physically heavy occupations

Abstract: Background The aim was to assess the rate at which waste collectors and municipal workers leave their job, to establish the outcome and to identify associated risk factors within work environment, health, lifestyle and marital status. Methods A questionnaire‐based survey among a cohort of 2,918 waste collectors and municipal workers was performed in 1994, with follow‐up 2.5 years later. Results Twenty‐five percent had left the job at follow‐up. Of these, 31% had changed jobs (associated with low decision autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 6 publications
3
50
1
1
Order By: Relevance
“…This could indicate a selection in the material, at least among the women, which could have diluted associations between work-related risk factors and symptoms. In a study of male waste collectors and municipal workers, different associations between occupational factors, health (including musculoskeletal symptoms), individual factors and unemployment, disability pension/long-term sick leave and early retirement pension, respectively, were found (Lund et al 2001). Thus, also for men, a dilution of some associations may have taken place.…”
Section: Methodological Considerationsmentioning
confidence: 87%
“…This could indicate a selection in the material, at least among the women, which could have diluted associations between work-related risk factors and symptoms. In a study of male waste collectors and municipal workers, different associations between occupational factors, health (including musculoskeletal symptoms), individual factors and unemployment, disability pension/long-term sick leave and early retirement pension, respectively, were found (Lund et al 2001). Thus, also for men, a dilution of some associations may have taken place.…”
Section: Methodological Considerationsmentioning
confidence: 87%
“…In a recent review, high age, being single, and low socioeconomic status were identified as demographic risk factors [2]. Lifestyle factors such as alcohol consumption [3], smoking, high or low BMI [4], and use of hypnotics/analgesics have also been related to disability pension [2]. Foreign citizenship, prior sickness absence [1], and low selfrated health [5] have further been identified as predictors.…”
Section: Introductionmentioning
confidence: 97%
“…The following work environmental risk factors have been identified: physical demands [10], heavy work, work in uncomfortable positions, long working hours, noise at work, and repetitive muscle strain [7]. Psychosocial work environmental factors such as mental job strain [7], non-stimulating work, substantial complexity [10], low decision latitude, high demands [5], lack of social support from supervisors [7], and low skill discretion [4] have further been identified as risk factors for disability pension. The effects of most of these factors differed for men and women.…”
Section: Introductionmentioning
confidence: 98%
“…Another paper from outside the field of economics is by Lund et al (2001). They look at the rates at which waste collectors and municipal workers leave their jobs, and identify associated risk factors within the work environment and health, life-style and marital status.…”
Section: Introductionmentioning
confidence: 99%